2017
DOI: 10.1080/02670844.2016.1235522
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of c-axis oriented AlN thin films at room temperature

Abstract: In this study, aluminium nitride (AlN) thin films were synthesised by plasma-enhanced reactive DC magnetron sputtering on glass and Si (100) substrates and the effect of bias voltages on the structural, optical and morphological properties of the coatings has been studied. According to the grazing angle XRD studies, AlN in hexagonal (wurtzite) structure has been obtained for all the coatings. ( 002) plane c-axis oriented films have been achieved at 150 and 175 V bias voltages. AFM analyses demonstrated that wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…For a front electrode with thin film solar cells, light trapping structure plays a decisive role in scattering the incoming light into the silicon absorber layer [1][2][3][4]. But it does not work for good transparent conducting oxides (TCOs).…”
Section: Introductionmentioning
confidence: 99%
“…For a front electrode with thin film solar cells, light trapping structure plays a decisive role in scattering the incoming light into the silicon absorber layer [1][2][3][4]. But it does not work for good transparent conducting oxides (TCOs).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to high refractive index, AlN has the characteristic of high transmittance. Many literatures [26][27][28] reported that AlN films with more than 80% transmittance in visible band can be obtained by DC magnetron sputtering technology. AlN films with high refractive index and light transmittance have excellent properties for optoelectronic applications, such as solar cell protective coatings [26] and heat dissipation material for high power lighting devices [29].…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, AlN has the characteristics of high thermal conductivity and exceedingly good electronic properties, which makes it an excellent material for high-power electronic devices [2,3]. Moreover, AlN along the C-axis has been used in surface acoustic wave devices due to its good piezoelectric properties [4]. In addition, the lattice constants and thermal expansion coefficient of an AlN crystal are similar to those of a GaN crystal, which makes the AlN crystal suitable as a substrate material for epitaxial growth of the GaN crystal [5].…”
Section: Introductionmentioning
confidence: 99%